PET guidance in prostate cancer radiotherapy: Quantitative imaging to predict response and guide treatment. Issue 3 (March 2016) - Cattaneo, G.M.; Bettinardi, V.; Mapelli, P.; Picchio, M.
Highlights: Determine the current application of PET in prostate cancer (PCa) management. Describe the state-of-the art of all issues related to the PET in PCa RT scenario. Analysis of PET quantification methods aiming at guiding individualized treatment. Abstract: Positron emission tomography (PET) allows a monitoring and recording of the spatial and temporal distribution of molecular/cellular processes for diagnostic and therapeutic applications. The aim of this review is to describe the current applications and to explore the role of PET in prostate cancer management, mainly in the radiation therapy (RT) scenario. The state-of-the art of PET for prostate cancer will be presented together with the impact of new specific PET tracers and technological developments aiming at obtaining better imaging quality, increased tumor detectability and more accurate volume delineation. An increased number of studies have been focusing on PET quantification methods as predictive biomarkers capable of guiding individualized treatment and improving patient outcome; the sophisticated advanced intensity modulated and imaged guided radiation therapy techniques (IMRT/IGRT) are capable of boosting more radioresistant tumor (sub)volumes. The use of advanced feature analyses of PET images is an approach that holds great promise with regard to several oncological diseases, but needs further validation in managing prostate diseases.